2002
DOI: 10.1034/j.1600-0609.2002.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Steroid‐refractory chronic idiopathic thrombocytopenic purpura associated with hepatitis C virus infection

Abstract: Given these findings, we recommend that HCVab is measured upon diagnosis of chronic ITP, and that splenectomy is planned in patients with HCVab in the event that prednisolone treatment is ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 27 publications
1
33
1
1
Order By: Relevance
“…30,31,37 Epidemiology Six cross-sectional studies have reported serologic evidence of HCV infection in 159 of 799 (20%) patients with a clinical diagnosis of CITP (Table 1). 30,31,[37][38][39][40] In the largest series published to date, HCV antibodies were identified in 76 (30%) of 250 patients fulfilling the ASH guideline criteria for CITP. 31 There were significant differences in demographic characteristics of patients with HCV-positive compared with HCV-negative CITP.…”
Section: Hcv Infectionmentioning
confidence: 99%
“…30,31,37 Epidemiology Six cross-sectional studies have reported serologic evidence of HCV infection in 159 of 799 (20%) patients with a clinical diagnosis of CITP (Table 1). 30,31,[37][38][39][40] In the largest series published to date, HCV antibodies were identified in 76 (30%) of 250 patients fulfilling the ASH guideline criteria for CITP. 31 There were significant differences in demographic characteristics of patients with HCV-positive compared with HCV-negative CITP.…”
Section: Hcv Infectionmentioning
confidence: 99%
“…Clinically, patients with Sjögren's syndrome and thrombocytopenia are significantly younger and have a higher tendency to have accompanying skin eruptions and anti-SS-B antibody than those without (7). On the other hand, the majority of patients with immune thrombocytopenic purpura related to HCV need treatment such as PSL and splenectomy, with the response to PSL much poorer than those unrelated to HCV (15). Thus, we would implicate the present case's thrombocytopenia in CHC rather than a complication of Sjögren's syndrome based on the following reasons: high titers of serum HCV RNA, negative anti-SS-A/SS-B antibodies, severe and recurrent thrombocytopenia in spite of PSL treatment, and high age at onset.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we would implicate the present case's thrombocytopenia in CHC rather than a complication of Sjögren's syndrome based on the following reasons: high titers of serum HCV RNA, negative anti-SS-A/SS-B antibodies, severe and recurrent thrombocytopenia in spite of PSL treatment, and high age at onset. PSL, interferon alpha (IFN-), and splenectomy are favored in the treatment of thrombocytopenia associated with CHC (15)(16)(17). Here, we chose PSL rather than IFN-because successful treatment with PSL for thrombocytopenia associated with HCV was reported without exacerbation of liver function (17); treatment with IFN-per se sometimes induces thrombocytopenia in CHC (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque no se conocen los mecanismos involucrados en el desarrollo de estos anticuerpos antiplaquetarios, se ha observado que el VHC tiene capacidad de unión a las plaquetas, al igual que el VIH (24)(25)(26)(27); esta característica del virus favorecería el desarrollo de nuevos antígenos sobre la superficie de las plaquetas mediante la modificación en la conformación de las glucoproteínas plaquetarias, lo cual propiciaría el desarrollo de anticuerpos autorreactivos (25,26). Otros mecanismos inmunoló-gicos que podrían estar involucrados en el desarrollo de esta púrpura trombocitopénica, son el depósito de complejos inmunes inespecíficos en la superficie plaquetaria (19,31) o la presencia de anticuerpos anticardiolipina (32), lo cual nos demuestra el carácter complejo de esta etiología.…”
Section: Hepatitis Viralunclassified